INFLUENCE TURNOVER INTENTION , BURDEN WORK, AND COMPETENCY TOWARDS EMPLOYEE PERFORMANCE PT. DINAMIKA SURYA BRIGHT STAR - Epicilia Angeline; Christian Axel; Felix Tanaka; Cut Fitri Rostina; Fauzi (Mount Hope Economic Global Journal, 2025)
In PT. Dinamika Surya Bintang Brilliant , research This investigate impact of turnover intention, burden work , and competence to performance employees . Research This aiming For learn How intention For go out from work (turnover intention), burden work , and competence impact on performance employees of PT. Dinamika Surya Bintang Brilliant . Decrease income during three year final show decline performance employee . Studies study This based on on trend decline income company during three year lastly , it is suspected related with performance bad employee .​ Studies study This use method approach quantitative with design descriptive . Method data collection used For send questionnaire to respondents are divided over 40 employees still and 30 employees contracts in the environment company . Testing validity And reliability instrument , testing assumption classic , analysis multiple linear regression , and testing partial And simultaneous (t-test and F-test) is all method analysis of the data used . all in all with using the SPSS program. Results studies study explain that competence and turnover intention partial own influence positive to performance employee . On the contrary , the burden Work No own significant influence​ in a way statistics to performance employee . However , the performance influenced in a way significant by third variable free the moment operate simultaneously . With coefficient determination of this model by 87.2 %, the proportion variation performance employee can explained by three component This .